Immigrant parents’ experiences and perspectives on the early childhood education stages in Nordic contexts - Samah M. Migdad; Kjersti Lea; Martin M. Sjøen (Nordic Journal of Comparative and International Education)
To explore the state of research on immigrant parents’ experiences in early childhood education (ECE) stages, we conducted a literature review through a qualitative meta-synthesis of 22 studies. Guided by sociocultural theory, which emphasizes the co-construction of meaning and the interplay between individual agency and social context, the synthesis highlights both the barriers immigrant parents face and opportunities for enhancing inclusion and support within Nordic ECE contexts. While the articles acknowledge these challenges, they also found that some parents increasingly appreciate Nordic ECE values and practices over time. Communication emerges as a central theme in the reviewed literature; it deeply impacts the integration process of immigrant parents in Nordic ECE systems. Synthesized findings across the studies highlight communication as a key factor shaping parents’ experiences within the categories of “initial experiences and adaptation,” “parental concerns,” and “cultural and social integration.” The review reveals a predominance of host-country researchers, the majority being female, with minority groups underrepresented, which could potentially lead to biases. Despite methodological limitations that impact the understanding of immigrant parents' experiences, the studies offer valuable insights into the parents’ reported experiences and provide a foundation for improving inclusivity and understanding in Nordic ECE.